PEMBERDAYAAN DAN PARTISIPASI MASYARAKAT MELALUI PENDIDIKAN DAN PELATIHAN DALAM PEMBANGUNAN DI DESA BANJAREJO KECAMATAN PAGELARAN KABUPATEN MALANG - Amatul Jadidah (JOURNAL OF COMMUNITY DEDICATION, 2024)
Community empowerment through education is one of the efforts to increase community awareness and participation in development. This study aims to determine how community empowerment through education can increase community awareness and participation in development. The method used in this study is a qualitative method. The results showed that community empowerment through education can increase community awareness and participation in development by increasing community knowledge and skills.